A gradient milled gasket for positive electrode coating
Patent Information
- Application Number
- CN202522541556.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2035-11-30
AI Technical Summary
[0002]在锂离子电池,尤其是磷酸铁锂体系电池的制造中,极片涂布是决定电池性能一致性的关键工序,为提高能量密度和生产效率,宽幅高速涂布已成为行业趋势,在正极涂布工艺中,通常会在极片的机尾(即集流体的边缘)区域涂覆一层陶瓷涂层,其主要作用是防止毛刺穿刺隔膜,提升电池安全性,然而,在该机尾陶瓷涂覆工序中,由于涂布模头与背辊之间存在横向(即垂直于涂布方向)的GAP(间隙)梯度,具体表现为:从活性材料料区,经过料区与陶瓷区的交界区,再到纯陶瓷边缘区,GAP值呈梯度递增,通常会增加0.1-0.3mm,这种GAP梯度是由设备安装、热变形及机械应力等综合因素造成的,难以彻底消除;
[0020]1.通过在基体上开设陶瓷流道铣槽区,使深槽低流阻补偿小GAP,浅槽高流阻抑制大GAP的逆向补偿原理,本垫片动态平衡了因横向GAP梯度造成的压力损失,使陶瓷浆料在模头出口处的横向挤出压力趋于均衡,实测可将陶瓷涂层的横向厚度波动率从±15%优化至≤±4.5%,边缘减薄率从28%压缩至5%以内,为后续工序提供了结构均匀的极片基础,上述实现了涂层横向厚度的高一致性;
Smart Images

Figure CN224912765U_ABST
Abstract
Description
Technical Field
[0001] This utility model relates to the field of lithium-ion battery electrode technology, and in particular to a gradient milled groove pad for positive electrode coating. Background Technology
[0002] In the manufacturing of lithium-ion batteries, especially lithium iron phosphate batteries, electrode coating is a key process that determines the consistency of battery performance. To improve energy density and production efficiency, wide-width high-speed coating has become an industry trend. In the positive electrode coating process, a ceramic coating is usually applied to the tail of the electrode (i.e., the edge of the current collector). Its main function is to prevent burrs from puncturing the separator and improve battery safety. However, in this tail ceramic coating process, there is a transverse (i.e., perpendicular to the coating direction) GAP (gap) gradient between the coating die and the back roller. Specifically, from the active material area, through the boundary between the material area and the ceramic area, and then to the pure ceramic edge area, the GAP value increases in a gradient, usually by 0.1-0.3 mm. This GAP gradient is caused by a combination of factors such as equipment installation, thermal deformation, and mechanical stress, and is difficult to completely eliminate.
[0003] Currently, the industry commonly uses equal-depth grooved gaskets. These gaskets have a uniform groove depth in the ceramic flow channel area. Under ideal conditions with uniform GAP, they can ensure uniform slurry outflow. However, in the actual GAP gradient environment described above, equal-depth gaskets reveal inherent defects: their constant flow resistance cannot compensate for varying GAP values. On the material area side with smaller GAP, the slurry outflow resistance is high, resulting in a thinner coating. On the ceramic edge side with larger GAP, the slurry outflow resistance is low, making it easy for leakage to occur, resulting in a thicker coating or even the formation of humps. This directly causes severe unevenness in the transverse thickness of the ceramic coating, with an edge thinning rate of up to 20%-30%.
[0004] This uneven thickness can cause a series of process and product quality problems:
[0005] Ceramic active material miscibility: In the interface region with uneven thickness, the hydrodynamics of the slurry becomes disordered. During the drying process, due to the difference in drying rate in different regions, lateral capillary flow is triggered, causing undesirable mixing of ceramic materials and active materials at the microscopic level, forming a "miscibility zone" (usually about 1.2 mm wide). The miscibility zone destroys the interface clarity and structural consistency of the coating, affects lithium-ion transport, and leads to increased battery internal resistance and decreased cycle performance.
[0006] Subsequent laser cutting defects: The inter-solubility zone and uneven coating structure will cause uneven absorption and reflection of laser energy in the subsequent laser cutting process. This can easily lead to defects such as incomplete cutting (the ceramic layer is not completely cut off) and cascading (the cutting stress causes cracks or peeling in the active material area). The defect rate is usually as high as 5%-8%, which seriously restricts the production yield.
[0007] To address the aforementioned issues, this application proposes a gradient milled groove pad for positive electrode coating. Utility Model Content
[0008] Based on the technical problems existing in the background art, this utility model proposes a gradient milled groove gasket for positive electrode coating.
[0009] This utility model proposes a gradient milled groove gasket for positive electrode coating, comprising a substrate and a ceramic flow channel milled groove area formed on the substrate, characterized in that: the groove depth of the ceramic flow channel milled groove area is inclined from one end to the other end, forming a gradient decrease along the direction from the adjacent active material area to the ceramic edge.
[0010] Preferably, the gradient decrease satisfies that the initial groove depth H1 at the adjacent material area end is greater than the final groove depth H2 at the ceramic edge end, and H1 / H2=1.1-1.5.
[0011] Preferably, the gradient-decreasing structure is a linear tilting structure, and the tilt angle of the linear tilting structure is θ = 5°-15°.
[0012] Preferably, the gradient decreasing structure is a stepped structure (202), which includes at least two depth steps with a depth difference Δ ≥ 0.05 mm between adjacent steps.
[0013] Preferably, the stepped structure has three levels, including a deep groove section near the material area end, a middle transition section, and a shallow groove section at the ceramic edge end, the depths of which respectively satisfy:
[0014] The depth of the step near the deep trench section is Ha=H1;
[0015] The step depth of the transition section is Hb = (H1 + H2) × 0.6 - 0.8;
[0016] The depth of the step near the shallow trench section is Hc=H2.
[0017] Preferably, the depth H1 of the deep trench section ranges from 0.4mm to 0.6mm, and the depth H2 of the shallow trench section ranges from 0.3mm to 0.5mm.
[0018] Preferably, the gradient decreasing structure covers 15%-50% of the width of the ceramic flow channel opening at each step in the milled groove area of the ceramic flow channel, matching the GAP gradient change area of the tail ceramic area.
[0019] The above-mentioned technical solution of this utility model has the following beneficial technical effects:
[0020] 1. By creating a ceramic flow channel milling groove area on the substrate, the deep groove with low flow resistance compensates for small gaps, while the shallow groove with high flow resistance suppresses large gaps. This gasket dynamically balances the pressure loss caused by the transverse gap gradient, making the transverse extrusion pressure of the ceramic slurry at the die outlet more uniform. Actual measurements show that the transverse thickness fluctuation rate of the ceramic coating can be optimized from ±15% to ≤±4.5%, and the edge thinning rate can be reduced from 28% to less than 5%. This provides a uniform electrode base for subsequent processes, and the above achieves high consistency of the transverse thickness of the coating.
[0021] 2. Due to the uniform coating thickness, the fluid flow in the interface area is stable, the drying kinetics are improved, and the lateral capillary flow that leads to material miscibility is effectively eliminated. Metallographic sectioning shows that the width of the miscibility zone can be reduced from more than 1.2 mm to less than 0.3 mm, and the miscibility occurrence rate is reduced from 8%-12% to less than 1%, which improves the clarity of the electrode interface and the consistency of electrochemical performance. The above measures inhibit the miscibility of ceramic active materials from the source.
[0022] 3. The uniform and dense ceramic coating provides a stable physical and energy absorption interface for laser cutting. During cutting, abnormalities no longer occur due to sudden changes in thickness and composition. This reduces the laser cutting defect rate, including incomplete cuts and entanglements, from the traditional 5%-8% to below 0.3%. At the same time, it also reduces the wear of the die-cutting blade, extends the tool life, and reduces the production capacity loss caused by downtime and cleaning. Overall, it improves production efficiency and yield, and completely solves the problem of defective laser cutting in subsequent processes. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the overall structure of a gradient milled groove gasket for positive electrode coating proposed in this utility model;
[0024] Figure 2 This is a schematic diagram of the linear tilted structure within the matrix of this utility model;
[0025] Figure 3 This is a schematic diagram of the stepped structure within the matrix of this utility model;
[0026] Figure 4 This is a schematic diagram of the processing structure of a gradient milled groove gasket for positive electrode coating proposed in this utility model.
[0027] Reference numerals: 10, substrate; 20, milled groove area of ceramic flow channel; 201, linear inclined structure; 202, stepped structure; 20a, deep groove section; 20b, shallow groove section. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this utility model clearer, the present utility model will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that these descriptions are merely exemplary and not intended to limit the scope of this utility model. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concept of this utility model.
[0029] Example 1
[0030] like Figure 1-4 As shown, the present invention proposes a gradient milled groove gasket for positive electrode coating, including a substrate 10 and a ceramic channel milled groove region 20 formed on the substrate 10. The groove depth of the ceramic channel milled groove region 20 is inclined from one end to the other end, forming a gradient decrease along the direction from the adjacent active material area to the ceramic edge.
[0031] This design is based on the pressure compensation principle in fluid mechanics. During the coating process, the slurry flows through the milled groove area 20 of the ceramic channel. Due to the inherent transverse gap gradient of the equipment, the actual channel height (GAP) increases from the material area to the ceramic edge. This will cause the slurry to flow too fast and the pressure to be too low in the area with large GAP, resulting in thickening of the coating edge or the generation of eddies.
[0032] The above-mentioned structure reduces the groove depth of the ceramic flow channel milling zone 20 in reverse, that is, gradually increases the flow resistance by gradually reducing the groove depth along the slurry outflow path. In the area where the GAP increases, the structure can compensate for the pressure loss caused by the increase in GAP by reducing the groove depth, thereby making the outlet pressure of the slurry at different positions in the lateral direction of the die head tend to be consistent, and finally achieving a uniform distribution of the coating thickness in the lateral direction, fundamentally suppressing material mutual solubility and cutting defects caused by uneven thickness.
[0033] In a specific embodiment, the gradient decrease satisfies that the initial groove depth H1 at the adjacent material area end is greater than the final groove depth H2 at the ceramic edge end, and H1 / H2=1.1-1.5;
[0034] The optimal range for limiting the groove depth ratio H1 / H2 to 1.1-1.5 is the one verified by extensive fluid simulation and experiments. When the ratio is below 1.1, the compensation effect is insufficient and cannot effectively balance the typical 0.1-0.3mm GAP gradient change, resulting in little improvement in coating uniformity. When the ratio is above 1.5, it will lead to excessively low flow resistance on the material side and excessively high flow resistance on the edge side, which may cause excessive extrusion of slurry on the material side and difficulty in extrusion on the edge side, or even blockage of the flow channel. Under this optimized ratio, the GAP gradient in actual production can be matched to achieve the best lateral pressure balance effect, ensuring that the coating thickness fluctuation rate is stably controlled within ±4.5%.
[0035] In a specific embodiment, the gradient decreasing structure is a linear tilting structure 201, and the tilt angle of the linear tilting structure 201 is θ = 5°-15°.
[0036] The linear tilted structure 201 provides a continuous and smooth flow resistance variation mode. The tilt angle θ is controlled between 5° and 15°, which ensures a stable transition of slurry flow and avoids abrupt changes in flow field and pressure. When the slurry flows through this linear tilted structure 201, the flow resistance it experiences increases linearly with the distance it travels. This gentle change is particularly suitable for working conditions where the GAP value also increases linearly. It can effectively guide the slurry streamline, reduce the generation of turbulence and dead zones, thereby obtaining a high-quality coating interface with a smooth transition and no abrupt changes.
[0037] Example 2
[0038] In a specific embodiment, the gradient decreasing structure is a stepped structure 202, which includes at least two depth steps, and the depth difference between adjacent steps is Δ≥0.05mm.
[0039] The stepped structure 202 achieves a step-by-step increase in flow resistance through discrete steps. Each step forms a small flow resistance abrupt change point, and the depth difference between adjacent steps Δ≥0.05mm ensures that each level has a significant flow resistance adjustment effect. This structure can effectively cope with nonlinear or step-changing GAP gradients. Its processing is simpler than that of linear structures, and it can flexibly adapt to different GAP change patterns by combining different numbers of steps. Multi-level steps distribute the total flow resistance change across multiple stages, which can maintain the overall stability of the flow better than single-level abrupt changes and prevent excessive shear force at a single interface from causing changes in slurry properties.
[0040] In a specific embodiment, the stepped structure 202 has three levels of steps, including a deep groove section 20a near the material area end, a middle transition section, and a shallow groove section 20b at the ceramic edge end, the depths of which respectively satisfy:
[0041] The depth of the step on the side near the deep trench section 20a is Ha=H1;
[0042] The step depth of the transition section is Hb = (H1 + H2) × 0.6 - 0.8;
[0043] The depth of the step on the side near the shallow trench section 20b is Hc=H2.
[0044] The deep channel section 20a is responsible for providing sufficient slurry flow on the side of the material zone with the smallest GAP, while the shallow channel section 20b applies sufficient flow resistance on the side of the ceramic edge with the largest GAP to suppress excessive slurry outflow. The intermediate transition section (depth Hb is 0.6 to 0.8 times the sum of H1 and H2) plays a key role in connecting the upper and lower sections. It makes the change in flow resistance more gradual and avoids the flow separation or eddy phenomenon that may be caused by jumping directly from the deep channel section 20a to the shallow channel section 20b. This three-level configuration of deep, medium and shallow can correspond to the three functional areas of material zone, boundary zone and ceramic zone, and realize regional pressure control.
[0045] In a specific embodiment, the depth H1 of the deep trench section 20a ranges from 0.4mm to 0.6mm, and the depth H2 of the shallow trench section 20b ranges from 0.3mm to 0.5mm.
[0046] This depth range is set for the rheological characteristics of commonly used high-viscosity ceramic slurries. H1 (0.4-0.6mm) ensures a sufficiently large flow cross-section on the material side to prevent high-viscosity slurry from clogging here. H2 (0.3-0.5mm) generates sufficient flow resistance to effectively limit the flow rate in the edge area, while preventing large particles in the slurry from clogging the flow channel due to excessively shallow flow channels. This range of values ensures that the gasket can work stably under a wide range of process parameters.
[0047] In a specific embodiment, the coverage width of each step of the gradient decreasing structure on the ceramic flow channel milling groove area 20 accounts for 15%-50% of the width of the ceramic flow channel opening, which matches the GAP gradient change area of the tail ceramic area.
[0048] The aforementioned width setting ensures that the pressure compensation effect can accurately cover the physical area where the GAP gradient change actually occurs. If the compensation area is too narrow, it cannot completely cover the entire GAP change zone, and the edge area will still have uneven thickness. If the compensation area is too wide, it may affect the stable flow channel area that does not need compensation, resulting in waste or even new unevenness. A width ratio of 15%-50%, determined through experiments, can ensure that the effective range of the gradient milling groove area 20 coincides spatially with the GAP gradient zone from the material area to the ceramic edge at the tail of the electrode mill, thereby achieving the optimal compensation effect.
[0049] In a specific embodiment, the substrate 10 is applied to the tail ceramic region of the positive electrode coating of the lithium iron phosphate system to suppress the mutual dissolution of ceramic active materials and abnormalities associated with laser cutting.
[0050] Lithium iron phosphate cathode slurry, due to its high solid content and unique rheological properties, is more sensitive to coating uniformity. This pad, through the ceramic flow channel milling groove region 20 structure opened on its substrate 10, can improve the lateral consistency of the ceramic coating when applied to this system. The uniform coating eliminates the lateral capillary flow driving force during the drying process, inhibiting the mutual solubility between ceramic and active materials from the source. At the same time, the coating with uniform thickness and clear interface provides a uniform physical and energy absorption interface for subsequent laser cutting, completely solving the problems of incomplete cutting and associated abnormalities caused by abrupt thickness changes and mutual solubility, reducing the laser cutting defect rate from 5%-8% to below 0.3%.
[0051] In a specific embodiment, the gasket is designed with a die for processing. The die has a groove with inclined sides, corresponding to the gasket. Figure 4 This can be seen from the text.
[0052] It should be understood that the above-described specific embodiments of this utility model are merely illustrative or explanatory of the principles of this utility model, and do not constitute a limitation thereof. Therefore, any modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and scope of this utility model should be included within the protection scope of this utility model.
Claims
1. A gradient milled groove gasket for positive electrode coating, characterized in that, The invention includes a substrate (10) and a ceramic channel milling groove area (20) formed on the substrate (10), characterized in that the groove depth of the ceramic channel milling groove area (20) is inclined from one end to the other end, forming a gradient decrease along the direction from the adjacent active material area to the ceramic edge.
2. The gradient milled groove gasket for positive electrode coating according to claim 1, characterized in that, The gradient decrease satisfies that the initial groove depth H1 at the adjacent material zone end is greater than the final groove depth H2 at the ceramic edge end, and H1 / H2=1.1-1.
5.
3. A gradient milled groove gasket for positive electrode coating according to claim 2, characterized in that, The gradient decreasing structure is a linear tilted structure (201), and the tilt angle of the linear tilted structure (201) is θ = 5°-15°.
4. A gradient milled groove gasket for positive electrode coating according to claim 2, characterized in that, The gradient decreasing structure is a stepped structure (202), which contains at least two depth steps with a depth difference Δ ≥ 0.05 mm between adjacent steps.
5. A gradient milled groove gasket for positive electrode coating according to claim 4, characterized in that, The stepped structure (202) has three levels of steps, including a deep groove section (20a) near the material area end, a middle transition section, and a shallow groove section (20b) at the ceramic edge end, the depths of which respectively satisfy: The depth of the step near the deep trench section (20a) is Ha=H1; The step depth of the transition section is Hb = (H1 + H2) × 0.6 - 0.8; The depth of the step near the shallow trench section (20b) is Hc=H2.
6. A gradient milled groove gasket for positive electrode coating according to claim 5, characterized in that, The depth H1 of the deep trench section (20a) ranges from 0.4mm to 0.6mm, and the depth H2 of the shallow trench section (20b) ranges from 0.3mm to 0.5mm.
7. A gradient milled groove gasket for positive electrode coating according to claim 6, characterized in that, The gradient decreasing structure covers 15%-50% of the width of the ceramic flow channel opening in the milled groove area (20) of the ceramic flow channel, which matches the GAP gradient change area of the tail ceramic area.